Marshall's Theory of Value and Distribution - Laughlin, J. Laurence (Quarterly Journal of Economics, 1887)
Journal Article Marshall's Theory of Value and Distribution Get access J. Laurence Laughlin J. Laurence Laughlin Search for other works by this author on: Oxford Academic Google Scholar The Quarterly Journal of Economics, Volume 1, Issue 2, January 1887, Pages 227–232, https://doi.org/10.2307/1880772 Published: 01 January 1887